SANITASI LINGKUNGAN MASYRAKAT SUKU AKIT DI DESA TITI AKAR KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Misliyanti "; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Akit community in Titiakar Village is an environmental empowerment. How unfit the environment in which the Akit tribe of Titiakar Village lives is clean. Clean water needs for bathing, washing, and cooking activities generally use rain water and well water. The condition of the well water is yellowish, smelly and brackish. Some wells have used electricity. Rainwater is an alternative to get clean water sources. Rainwater from the roof of the house is channeled to the storage tank. Clean water is very difficult to obtain. So that the Akit people must take the initiative to collect rainwater. However, rain certainly does not always fall, another way is to share wells with neighbors. The formulation of the problem in this study is how to look at the environmental sanitation of the Akit Tribe community of Titi Akar Village and how the net meaning of the Akit Tribe community of Titi Akar Village. This study uses the theory of social behavior that is behavior can be understood as a concrete action that exists in humans which is manifested from the individual in the form of an attitude of the limbs or in the form of spontaneous speech without planned or thought and without coercion. Researchers used descriptive qualitative analysis by assigning 5 research subjects to 4 informants and 1 key informant who were taken intentionally (purposive sumpling) with the criteria set. Keywords: Environmental Sanitation. Akit tribe. Titi Akar Village.